Financial convergence in the Asia Pacific - Ibrahim, Juliana (2013)
The issues pertaining to the convergence of the financial sector as a result of economic co-operations and integrations in the emerging countries especially Asia Pacific emerge and yet to be explored. This is due to theoretical and empirical work on finance and growth which provide strong evidence that financial development is conducive to economic growth. There are many theory and empirical applications on per capita income convergence. However,there is neither a theory of financial system convergence, nor of an ‘optimum’financial system. The issues whether the Asia Pacific countries have achieved a certain degree of convergence in their financial sector will provide some insights into research questions which are particularly relevant both theoretically and policy reasons. Convergence is important in alleviating poverty and potential financial crisis, and sustaining the growth momentum in the region. At the same time, as the Asia Pacific’s financial sector converges, it is seen as a contribution to the global economy. The answer to convergence also relates to the validity of the centre-periphery growth model. This study evaluates the convergence patterns of the Asia Pacific financial developments from the financial sector perspective and examines how the countries are performing financially, relative to one another. For comparison purposes, by employing ‘Barro regressions’ model and Bernard and Durlauf (1995)’s stochastic convergence model, this study evaluates Asia Pacific’s financial sector cross-sectional and time series convergence from the period 1980 until 2009 for all three income groupings by examining: the cross country financial convergence to the common steady-state or individual steady-state level through β-convergence; the cross country financial convergence to a common equilibrium by employing σ-convergence; the financial convergence of the individual Asia Pacific country to its group’s mean level by considering bi-variate stochastic convergence; and group (regional) financial convergence towards their group’s mean level by estimating stochastic panel convergence. Simultaneously, hierarchical agglomerative cluster analysis is performed to identify the existence of club convergence among the countries. The Barro-regression results support absolute and conditional financial convergence for the Asia Pacific. Meanwhile, when examine individual stochastic convergence towards their average financial development levels, evidence of divergence can be found for almost all of the countries, with little evidence of convergence as catching-up for a small number of countries in the Asia Pacific, even after taking into account their heterogeneity factors. Based on the hierarchical cluster results, it is shown that the countries in the Asia Pacific are forming separate convergence clubs, based on their income per capita performance. The countries with a relatively well-developed financial system seems to be converging and forming the club with richer countries compared to the countries with relatively under-developed financial sector. This suggests that regional convergence of the financial sector is important for the growth of the Asia Pacific countries, particularly important especially to the middle- and low-income countries. After taking into account the heterogeneity factors of the Asia Pacific countries, it can be concluded that those countries with a relatively well-developed financial sector tend to catch-up with the richer countries, but poor countries with a relatively under-developed financial sector are less likely to catch-up. Hence, convergence process in the relatively lower-income countries might be very slow. This result supports the cetreperiphery growth model. It explains the reason as to why intra-regional differences persist or even widen over time due to agglomeration effects driven by maybe low financial sector’s costs and strong economies of scale (increasing returns) in the Asia Pacific countries which might be due to geographical, political or other factors.